Experiences of critical incidents among female and male firefighters. Issue 2 (April 2015) - Jacobsson, Ann; Backteman-Erlanson, Susann; Brulin, Christine; Hörnsten, Åsa
Highlights Fire fighters have described experiences of critical incidents. Traffic accidents, fire and other fatal incidents were mentioned as overwhelming situations. Risk of delay due to lack of training and lack of medical education was mentioned. Lack of resources and organizational problems were mentioned as causing risks. Several firefighters expressed frustration over being assaulted and threatened.